WNT7A Regulation by miR-15b in Ovarian Cancer. - James A MacLean; Mandy L King; Hiroshi Okuda; Kanako Hayashi (PLoS ONE, 2016)
WNT signaling is well known to play an important role in the regulation of development, cell proliferation and cell differentiation in a wide variety of normal and cancerous tissues. Despite the wealth of knowledge concerning when and where various WNT genes are expressed and downstream events under their control, there is surprisingly little published evidence of how they are regulated. We have recently reported that aberrant WNT7A is observed in serous ovarian carcinomas, and WNT7A is the sole ligand accelerating ovarian tumor progression through CTNNB1 (β-catenin)/TCF signaling in the absence of CTNNB1 mutations. In the present study, we report that WNT7A is a direct target of miR-15b in ovarian cancer. We showed that a luciferase reporter containing the putative binding site of miR-15b in the WNT7A 3'-UTR was significantly repressed by miR-15b. Mutation of the putative binding site of miR-15b in the WNT7A 3'-UTR restored luciferase activity. Furthermore, miR-15b was able to repress increased levels of TOPFLASH activity by WNT7A, but not those induced by S33Y. Additionally, miR-15b dose-dependently decreased WNT7A expression. When we evaluated the prognostic impact of WNT7A and miR-15b expression using TCGA datasets, a significant inverse correlation in which high-expression of WNT7A and low-expression of miR-15b was associated with reduced survival rates of ovarian cancer patients. Treatment with decitabine dose-dependently increased miR-15b expression, and silencing of DNMT1 significantly increased miR-15b expression. These results suggest that WNT7A is post-transcriptionally regulated by miR-15b, which could be down-regulated by promoter hypermethylation, potentially via DNMT1, in ovarian cancer.